2015
DOI: 10.1186/s41205-015-0002-4
|View full text |Cite
|
Sign up to set email alerts
|

3D printed ventricular septal defect patch: a primer for the 2015 Radiological Society of North America (RSNA) hands-on course in 3D printing

Abstract: Hand-held three dimensional models of the human anatomy and pathology, tailored-made protheses, and custom-designed implants can be derived from imaging modalities, most commonly Computed Tomography (CT). However, standard DICOM format images cannot be 3D printed; instead, additional image post-processing is required to transform the anatomy of interest into Standard Tessellation Language (STL) format is needed. This conversion, and the subsequent 3D printing of the STL file, requires a series of steps. Initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 5 publications
0
23
0
Order By: Relevance
“…For the procedures that require a complex form of surgical patch, the required patch can be graphically designed and printed preoperatively. 23 The 3D print patch model can be used as the template for trimming the surgical patch to be sewn on the patient's heart either before or during the surgery. Furthermore, newly developed surgical procedures can be tested on 3D print models before actual trial on patients.…”
Section: Discussionmentioning
confidence: 99%
“…For the procedures that require a complex form of surgical patch, the required patch can be graphically designed and printed preoperatively. 23 The 3D print patch model can be used as the template for trimming the surgical patch to be sewn on the patient's heart either before or during the surgery. Furthermore, newly developed surgical procedures can be tested on 3D print models before actual trial on patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the papers of [13,14], those areas that have benefited from LM are presented, including surgical planning, tissue replacement, pathologic assessment, education, and medical research. In [15], a practical LM procedure had been presented to create a heart model and a fixation patch, which were used in a remedy operation in an infant's heart. In the procedure, the researchers used a segmentation software to extract the blood pools of the heart and major vessels from the input computerized tomography (CT) scan data.…”
Section: Related Workmentioning
confidence: 99%
“…In the research presented in [6,7,[13][14][15][16][17], the scanned objects are contained in volume data sets. Before the LM processes starts, they have to be converted into polygonal representations to match the input data format of the slicers.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…They are relatively simple to print from contrast-enhanced CT, MRI and more recently, echocardiography [3, 17, 40, 41, 4547]. Kim et al reported the utility of 3D printed models for occluder device sizing and selection of the approach to cross the defect in cases of a muscular VSD and a fenestrated ASD with a large atrial septal aneurysm [48].…”
Section: Cardiovascular Applicationsmentioning
confidence: 99%